Survival Rate of pure zirconia and titanium zirconium alloy implants: Systematic Review - Sigcho, Diego (2019)
Objective: to systematically review in dental literature the survival rate of Zirconium and titanium zirconium alloy (Ti-Zr) implants. Methods: Clinical studies from the Pubmed, Embase and Cochrane databases, were selected by three researchers with inclusion criteria: Zirconia or Ti-Zr alloy implants, with a minimum of 1 year of follow-up evaluating survival rates, and exclusion criteria: laboratory, zygomatic and patients with systemic diseases. The agreement between the examiners was evaluated using the Kappa statistical test. We perform an i2 heterogeneity analysis, a random and fixed effect model using survival rates of both types of implants and Cochrane risk of bias tool. Results: 1755 articles were found from the initial search and 23 studies were included. Inter examiner agreement of kappa test was 72%. The survival rate of the titanium alloy and zirconia alloy was 97% and 90.3% for zirconia implants. In both types of models, the survival rate of the TiZr implant type was slightly higher than the other types of implants, and the 95% confidence interval. Analysis of risk of bias showed low risk. Conclusion: The data obtained in this study shows that TiZr alloy Zr implants presented high survival rates, furthermore clinical studies with longer follow-up are necessary to support the use of Zr implants.